Pengaruh Strategi Pemasaran Dan Harga Terhadap Keputusan Pembelian Melalui Diskon Motor Di Dealer Yamaha PT Thamrin Mukomuko - Celsi Karmila Sari; Emil Salim; Dori Mitra Candana (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research aims to test how much influence marketing strategy and price have on purchasing decisions through motorbike discounts at Yamaha dealer PT. Thamrin Mukomuko. The data collection method is through surveys and distributing questionnaires, with a sample of 66 respondents. The analytical method used is the structural equation model using smartpls. The research results obtained show a significant influence of marketing strategy on discounts. There is a significant influence of price on discounts. There is a significant influence of marketing strategy on purchasing decisions. There is a significant influence of price on purchasing decisions. There is a significant influence of discounts on purchasing decisions. There is a significant influence of marketing strategy on purchasing decisions through discounts. There is a significant influence of price on purchasing decisions through discounts.